2009
DOI: 10.1021/ja904052q
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Glycan Receptor Recognition and Specificity Switch for Avian, Swine, and Human Adapted Influenza Virus Hemagglutinins: A Molecular Dynamics Perspective

Abstract: Hemagglutinins (HA’s) from duck, swine, and human influenza viruses have previously been shown to prefer avian and human glycan receptor analogues with distinct topological profiles, pentasaccharides LSTa (α-2,3 linkage) and LSTc (α-2,6 linkage), in comparative molecular dynamics studies. On the basis of detailed analyses of the dynamic motions of the receptor binding domains (RBDs) and interaction energy profiles with individual glycan residues, we have identified ∼30 residue positions in the RBD that present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 67 publications
2
42
0
Order By: Relevance
“…MD simulations provide detailed information on the molecular structures and unbinding pathways that govern the interaction forces. In free simulations we observed that each receptor takes a slightly different conformation, although hydrogen bonds between four HA residues (Tyr98, Gly135, Ser136, and Asn137) and the receptor were always present, which is consistent with previous simulations (21,22). These four amino acids belong to the base and loop 130 of the HA receptor-binding pocket and are highly important for binding to the receptor (1).…”
Section: Discussionsupporting
confidence: 88%
“…MD simulations provide detailed information on the molecular structures and unbinding pathways that govern the interaction forces. In free simulations we observed that each receptor takes a slightly different conformation, although hydrogen bonds between four HA residues (Tyr98, Gly135, Ser136, and Asn137) and the receptor were always present, which is consistent with previous simulations (21,22). These four amino acids belong to the base and loop 130 of the HA receptor-binding pocket and are highly important for binding to the receptor (1).…”
Section: Discussionsupporting
confidence: 88%
“…The glycan microarray assay can provide more detailed information for mutations that require more detailed characterization. It should also be noted that bioinformatics approaches for in silico assessment of receptor specificity is emerging (Chandrasekaran et al, 2008; Newhouse et al, 2009; Xu et al, 2009), and may ultimately be of utility for large-scale analysis of sequence information once the in silico assessment of receptor specificity is documented to be a reliable predictor of receptor specificity assessed with laboratory assays.…”
Section: Relevance Of H5n1 Receptor Specificity To the Pandemic Potenmentioning
confidence: 99%
“…MD simulations were performed in AMBER 12 (28) with the AMBER ff99SB force field (29,30). The docked structure of the Topo II␣ ATPase domain with (ϩ)-rutamarin was used as the initial coordinates for MD simulations.…”
Section: Methodsmentioning
confidence: 99%